2015
DOI: 10.1037/pas0000036
|View full text |Cite|
|
Sign up to set email alerts
|

Empirical recommendations for improving the stability of the dot-probe task in clinical research.

Abstract: The dot-probe task has been widely used in research to produce an index of biased attention based on reaction times (RTs). Despite its popularity, very few published studies have examined psychometric properties of the task, including test-retest reliability, and no previous study has examined reliability in clinically anxious samples or systematically explored the effects of task design and analysis decisions on reliability. In the current analysis, we used dot-probe data from 3 studies in which attention bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
314
5
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(342 citation statements)
references
References 47 publications
21
314
5
2
Order By: Relevance
“…Researchers have proposed measures of attentional bias (e.g., Compton, 2000;Iacoviello et al, 2014;Koster et al, 2006;Zvielli, Bernstein, & Koster, 2014) with differing psychometric properties (e.g., Iacoviello et al, 2014;Price et al, 2014). In order to determine the psychometric properties of our measure of bias we conducted split-half reliability analysis (Nunnally, 1978).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have proposed measures of attentional bias (e.g., Compton, 2000;Iacoviello et al, 2014;Koster et al, 2006;Zvielli, Bernstein, & Koster, 2014) with differing psychometric properties (e.g., Iacoviello et al, 2014;Price et al, 2014). In order to determine the psychometric properties of our measure of bias we conducted split-half reliability analysis (Nunnally, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…To examine this three-way interaction further, we computed a bias score. However, recent research suggests investigators should examine the psychometric properties of their bias score (e.g., Price et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, extant procedures for assessing AB by using reaction-time indices are insufficiently reliable to detect changes in AB (e.g., Dear, Sharpe, Nicholas, & Refshauge, 2011;Schmukle, 2005;Staugaard, 2009;Waechter, Nelson, Wright, Hyatt, & Oakman, 2014). New reaction-time methods for quantifying AB have emerged (Price et al, 2015;Zvielli, Bernstein, & Koster, in press) that conceptualize AB as a dynamic process rather than a static trait. Preliminary research involving these new methods of measuring AB yield modest, but larger, internal reliability estimates vis-à-vis traditional indices of AB that yield near-zero estimates (Zvielli et al, in press).…”
Section: Theoretical and Clinical Implicationsmentioning
confidence: 97%
“…The finding for attentional bias is not surprising as previous research has been inconsistent, and some studies have shown no link with consumption (Field et al, 2007;Fadardi & Cox, 2009;Field et al, 2009;Hardman et al, 2013). Questions have also been raised regarding the reliability of the dot probe task (Schmulke, 2005;Price et al, 2014).…”
Section: Discussionmentioning
confidence: 99%